IDENTITY CRISIS IN LEWIS CARROLL’S “ALICE THROUGH THE LOOKING GLASS” - Andreas Tano; Gustaman Saragih (INFERENCE: Journal of English Language Teaching, 2020)
This research aims at showing the connection between the characters’ reality and fantasy on identity crisis in Alice through the Looking-Glass novel by Lewis Carroll. Thus, the conducted research was analyzed using qualitative method with the approach of psychoanalytical literary criticism: Psychoanalysis by Freud as well as the theory of Psychosocial Development by Erikson to seek the identity crisis of the character Alice. As the conclusion of the research; 1) Alice’s ‘ego’ cannot manage her ‘id’ which is difficult to be gratified in reality that triggers Alice overreact her defense mechanisms; 2) Alice’s fantasy works as a defense mechanism which is caused by her unfulfilled wishes in reality; 3) It is revealed that Alice experiences identity crisis at the phase of autonomy versus doubt and shame as well as initiative versus guilt which influences her behaviors, resulting Childhood Onset schizophrenic (COS) personality disorder.Keywords: identity crisis; psychoanalysis; interpretation of dreams; personality disorder; schizophrenia